Pengaruh Return On Asset, Debt To Equity Dan Ukuran Perusahaan Terhadap Price To Book Value Pada Sektor Transportasi Dan Logistik Tahun 2019-2023 - Nurhadyanti, Siti; Wirman, Wirman (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the influence of Return on Asset (ROA), Debt to Equity Ratio (DER), and Firm Size on Price to Book Value (PBV) in transportation and logistics companies listed on the Indonesia Stock Exchange during the period of 2019–2023. The research adopts a quantitative approach using multiple linear regression analysis. Data were collected from annual financial reports, with 55 observations selected through purposive sampling. The results show that simultaneously, ROA, DER, and Firm Size significantly affect PBV. However, partially, only DER has a significant and positive effect on PBV, while ROA and Firm Size do not show a significant impact. The Adjusted R Square value of 0.938 indicates that 93.8% of the variation in PBV can be explained by the three independent variables. These findings highlight the importance of capital structure as the main determinant of firm value, particularly during periods of economic uncertainty.